Trends and Patterns of Pancreatic Cancer Prevalence at Benghazi Medical Center: A Retrospective Analysis (2018–2024) - Nagwa Mohamed; Lehmidi, Tareq; Lobna Elfergani; Aya Albadry; Ghada Alramly; Hajer Aishhebi; Nada Alqetrani; Abeer Amer (AlQalam Journal of Medical and Applied Sciences, 2025)
Pancreatic cancer is a highly lethal malignancy with a poor prognosis worldwide. Despite its clinical importance, there is limited regional data available regarding its demographic and histopathological patterns in Libya. This study aimed to analyze the demographic characteristics, clinical presentation, and histological subtypes of pancreatic cancer in patients admitted to Benghazi Medical Center between 2018 to 2024. A cross-sectional analysis was conducted on 114 cases of histologically confirmed pancreatic cancer. Data were collected from hospital archives after obtaining ethical approvals. The variables assessed included age, gender, geographic location, disease stage at diagnosis, and histopathological subtypes. Descriptive statistical analysis was conducted utilizing Microsoft Excel 2016. The incidence of pancreatic cancer peaked in the 55–64 age group, with a notable male predominance. Most cases originated from Benghazi, followed by Al-Baida and Al-Maraj. The majority of patients (66.67%) presented with advanced-stage (Stage 4) disease at the time of diagnosis. The most common subtype in terms of histology was adenocarcinoma (65%), which was followed by intraductal papillary mucinous neoplasm (23%). These findings highlight the predominance of late-stage diagnosis and underscore significant demographic and histological trends in pancreatic cancer within the studied population. Further research is warranted to explore factors contributing to gender disparities and regional variations in incidence.